Clinical characteristics of catamenial and non‐catamenial thoracic endometriosis‐related pneumothorax. Issue 8 (26th August 2015) - Fukuoka, Mizuki; Kurihara, Masatoshi; Haga, Takahiro; Ebana, Hiroki; Kataoka, Hideyuki; Mizobuchi, Teruaki; Tatsumi, Koichiro
Abstract Background and objective A major pathogenic factor for catamenial pneumothorax is thoracic endometriosis. However, thoracic endometriosis‐related pneumothorax (TERP) can develop as either catamenial or non‐catamenial pneumothorax (CP). Therefore, the aim of this study was to elucidate the clinical differences between catamenial and non‐catamenial TERP. Methods The clinical and pathological data in female patients who underwent video‐assisted thoracoscopic surgery at the Pneumothorax Research Center during an 8‐year period were retrospectively reviewed. This study included 150 female patients with surgico‐pathologically confirmed TERP. The subjects were divided into two groups, those having all of the pneumothorax episodes in the catamenial period (CP group) and those who did not (non‐CP group). We compared the clinical characteristics and surgico‐pathological findings between these two groups. Results Of the 150 TERP patients, 55 (36.7%) were classified in the CP group, and 95 (63.3%) in the non‐CP group. In regard to the locations of endometriosis, all TERP patients had diaphragmatic endometriosis, while pleural implantation was recognized in 34 of the 55 (61.8%) patients in the CP group and 42 of the 95 (44.2%) patients in the non‐CP group (P < 0.05). Conclusions A significant difference in the proportion of patients with pleural endometriosis was observed between catamenial and non‐catamenial TERP. The ectopic sites of the endometriosis may be responsible for the timing of the pneumothorax episodes.